PHENOMENOLOGICAL STUDY ON FACTORS AND EFFECTS OF INTERNET ADDICTION AMONG UNIVERSITY STUDENTS - Nabisah Ibrahim; Noor Azizah Ahmad; Siti Alwaliyah Mansor (Journal of Islamic, Social, Economics and Development, 2024)
This study investigates the factors contributing to internet addiction among university students, and its effects on their academic, social, and psychological well-being. Seven undergraduate students aged 20 to 26 participated in in-depth interviews. The findings revealed three key factors: academic pressures, social connection, and psychological distress. Academic pressures, driven by overwhelming coursework and academic excellence, led students to turn to the internet as a temporary escape. Social isolation, particularly during late-night study sessions, compelled students to seek virtual companionship through social media platforms. Psychological distress, including stress and anxiety, further fuelled internet addiction. The study highlights the need for tailored interventions and support systems, focusing on stress and time management, promoting offline social interactions, and addressing mental health needs. Future research should consider longitudinal studies, com